Preparation method of binder-free sodium iron phosphate modified iron negative electrode and application thereof
Patent Information
- Application Number
- CN202611153797.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明针对目前水系铁金属电池铁负极循环使用过程中的诸多技术缺陷,提供了一种无粘结剂的磷酸铁钠修饰铁负极的制备方法及其在组装水系铁金属电池中的应用,用于有效解决传统水系铁金属电池铁负极在充放电循环过程中存在的严重腐蚀、析氢副反应、界面极化严重、铁离子沉积不均匀及循环稳定性差等技术问题,同时克服传统粉体电极制备工序繁琐、依赖粘结剂和导电剂、活性物质易脱落、界面阻抗大的技术短板
[0011]进一步地,所述水系铁金属电池为水系铁金属对称纽扣电池或水系铁金属全电池,其中水系铁金属对称纽扣电池以硫酸亚铁水溶液为电解液,磷酸铁钠修饰铁负极同时作为正极,搭配玻璃纤维隔膜完成对称纽扣电池组装;水系铁金属全电池体系以硫酸亚铁水溶液为电解液,以铁基普鲁士蓝类似物或硫单质为正极,搭配玻璃纤维隔膜完成全电池组装。
Smart Images

Figure CN122991970A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrode preparation technology for aqueous energy storage batteries, specifically relating to a method for preparing a binder-free sodium iron phosphate modified iron anode and its application. Background Technology
[0002] In existing commercial energy storage systems, lithium-ion batteries dominate the market due to their superior energy density and cycle performance. However, this system relies on flammable and explosive organic electrolytes, posing significant safety hazards and making it unsuitable for large-scale energy storage scenarios with high safety requirements. Compared to lithium-ion batteries, aqueous iron-metal batteries offer significant advantages, such as abundant iron reserves in the Earth's crust, wide availability, low cost, and extremely high theoretical specific capacity. Furthermore, aqueous iron-metal batteries use pure aqueous electrolytes, completely eliminating the safety risks of combustion and explosion associated with organic electrolytes. They possess high intrinsic safety, are environmentally friendly, and have a simple manufacturing process, making them a promising new low-cost and safe energy storage battery system with great commercial potential.
[0003] In the prior art, patent document CN201811465403.8 discloses an alkaline secondary battery iron-based negative electrode plate, its preparation method, and an alkaline secondary battery using the iron-based negative electrode plate. The iron-based negative electrode plate contains elemental sulfur, iron-based active materials, additives, conductive agents, and binders. Elemental sulfur is used as both an additive and a pore-forming agent. The alkaline secondary battery assembled based on this iron-based negative electrode plate has excellent safety, ultra-long cycle life, and good resistance to over- and over-discharge. The technical solution in this patent document adds conductive agents and binders during the preparation of the iron-based negative electrode plate. Patent document CN202411633740.9 discloses a chloride salt etching solution, an iron anode, and its preparation method. The method involves immersing foamed iron in the chloride salt etching solution for etching, followed by annealing to generate micron-sized particles on the surface of the foamed iron. This integrated electrode, constructed without an external iron source, exhibits good conductivity. The combination of the three-dimensional framework structure of the foamed iron and the micron-sized iron(III) oxide particles increases the specific surface area of the material, mitigates electrode structure changes during cycling, and improves the rate performance, specific capacity, and cycle stability of the electrode. However, this patent document's technical solution achieves the construction of a highly conductive electrode without an external iron source using a foamed iron matrix. It does not involve any related records of preparing sodium iron phosphate-modified iron anodes based on foamed iron, nor does it provide any technical inspiration for using the prepared sodium iron phosphate-modified iron anodes to assemble aqueous iron-metal batteries to significantly improve their long-cycle performance. Patent document CN202111517787.5 discloses a low-temperature resistant aqueous nickel-iron battery. The battery system includes a nickel oxide / carbon composite thin film positive electrode, a foamed iron negative electrode, and an antifreeze electrolyte. By adjusting the concentration ratio of highly polar potassium hydroxide electrolyte in the electrolyte, the original hydrogen bond network and the solvation structure of ions in the solvent are broken, which can significantly reduce the freezing point of the electrolyte and ensure its excellent ionic conductivity and reversible electrochemical reaction characteristics under low temperature conditions, thereby realizing the construction of a high-performance low-temperature resistant nickel-iron battery. However, the technical solution of this patent document only involves using foamed iron as the negative electrode of the aqueous nickel-iron battery, and does not involve any record of preparing sodium iron phosphate modified iron negative electrode based on foamed iron. At the same time, there is no relevant technical inspiration for using the prepared sodium iron phosphate modified iron negative electrode to assemble an aqueous iron metal battery to significantly improve the long-cycle service performance of the aqueous iron metal battery.
[0004] Currently, aqueous iron-metal batteries are still limited by the poor interfacial stability of the iron anode. During charge and discharge, severe interfacial polarization, hydrogen evolution side reactions, and substrate self-corrosion are prone to occur, accompanied by disordered iron dendrite growth, which seriously impairs the battery's cycle life and electrochemical reversibility. To address these technical challenges, this invention employs a single precursor hydrothermal process to construct an integrated iron-sodium phosphate modified layer of phosphate iron mineral phase on the surface of an iron-based substrate in situ. This eliminates the need for conductive agents and binders, effectively optimizing the electrode conductive network, reducing interfacial impedance, accelerating iron ion intercalation / deintercalation kinetics, and suppressing anode corrosion and interfacial degradation. This significantly improves the structural stability and long-cycle performance of the aqueous iron-metal battery anode. No related reports have been published in this area yet. Summary of the Invention
[0005] This invention addresses numerous technical shortcomings in the cycling process of iron anodes in current aqueous iron-metal batteries by providing a binder-free method for preparing sodium iron phosphate-modified iron anodes and their application in assembling aqueous iron-metal batteries. This method effectively solves the technical problems of severe corrosion, hydrogen evolution side reactions, severe interfacial polarization, uneven iron ion deposition, and poor cycle stability in traditional aqueous iron-metal battery anodes during charge-discharge cycling. It also overcomes the technical shortcomings of traditional powder electrode preparation, such as cumbersome processes, reliance on binders and conductive agents, easy detachment of active materials, and high interfacial impedance. This invention employs a simple and controllable high-temperature hydrothermal in-situ growth strategy to construct a highly crystalline sodium iron phosphate-modified layer on the surface and inside the pores of a self-supporting iron-based substrate. This results in a structurally stable, tightly bonded, integrated sodium iron phosphate-modified iron anode, effectively improving the ion transport efficiency and electrochemical reversibility of the aqueous iron-metal battery anode, achieving ultra-long stable cycling of the aqueous iron-metal battery. This provides a novel technical solution for the large-scale preparation and commercial application of high-performance, low-cost, and long-life aqueous energy storage batteries.
[0006] To solve the above-mentioned technical problems, this invention adopts the following technical solution: a method for preparing a binder-free sodium iron phosphate modified iron anode. The specific preparation steps are as follows: a sodium dihydrogen phosphate precursor mixed solution is prepared; a hydrothermal synthesis process is used to grow sodium iron phosphate active material in situ on the surface and internal pores of a pretreated iron-based conductive substrate, wherein the iron-based conductive substrate is foamed iron; after the hydrothermal reaction, the substrate is cooled to room temperature, and then cleaned and dried to obtain the sodium iron phosphate modified iron anode. This sodium iron phosphate modified iron anode can be directly used as an anode sheet for assembling aqueous iron-metal batteries. It uses a reaction system with a single precursor, sodium dihydrogen phosphate, without the addition of additional salts, eliminating the need for additional conductive agents and binders for coating and sheet preparation. The three-dimensional interconnected iron-based conductive matrix constructs a continuous high-speed conductive network, which firmly bonds the sodium iron phosphate active material to the iron-based conductive matrix interface, inhibiting the pulverization, shedding, and peeling of the active material during charging and discharging. The in-situ grown sodium iron phosphate mineral phase has good hydrophilicity, which helps the desolvation of ferrous ions, effectively optimizing the ion transport behavior at the electrode interface, reducing interfacial impedance, accelerating electrochemical kinetics, and significantly alleviating the corrosion, passivation, and capacity decay problems of the aqueous iron metal battery anode during cycling. It overcomes the technical bottlenecks of traditional powder electrode preparation processes, poor interfacial contact, weak structural stability, and short cycle life, thereby greatly improving the reversible capacity and long-cycle stability of aqueous iron metal batteries.
[0007] Furthermore, the concentration of the sodium dihydrogen phosphate precursor mixed solution is 2~5 mol / L, and its solvent is a mixed solvent system of deionized water and ethylene glycol with a volume ratio of 0.5~4:1.
[0008] Furthermore, the pretreatment process of the iron-based conductive substrate involves immersing the iron-based conductive substrate in a dilute hydrochloric acid solution to remove the oxide layer and impurities on the surface of the iron-based conductive substrate. The concentration of the dilute hydrochloric acid solution is 0.5~2 mol / L, and the immersion activation time is 30~120s. After the immersion activation is completed, the iron-based conductive substrate is alternately cleaned with deionized water and ethanol and then dried for later use.
[0009] Furthermore, the specific process of the hydrothermal synthesis is as follows: the pretreated iron-based conductive matrix is completely immersed in a sodium dihydrogen phosphate precursor mixed solution, and then transferred to a hydrothermal reactor for hydrothermal reaction at 200~230℃ for 8~14h.
[0010] The present invention relates to the application of the binder-free sodium iron phosphate modified iron anode in the assembly of aqueous iron metal batteries.
[0011] Furthermore, the aqueous iron-metal battery is an aqueous iron-metal symmetrical button cell or an aqueous iron-metal full cell. The aqueous iron-metal symmetrical button cell uses an aqueous solution of ferrous sulfate as the electrolyte, and sodium iron phosphate modifies the iron anode as the positive electrode, and is assembled with a glass fiber separator to complete the symmetrical button cell assembly. The aqueous iron-metal full cell system uses an aqueous solution of ferrous sulfate as the electrolyte, and uses an iron-based Prussian blue analog or elemental sulfur as the positive electrode, and is assembled with a glass fiber separator to complete the full cell assembly.
[0012] Compared with existing technologies, this invention has the following advantages and beneficial effects: The preparation process is simple and controllable, the process is concise, the preparation cost is low, the reaction parameters have a wide adjustable range, and it is suitable for large-scale mass production. This invention constructs a sodium iron phosphate functional modification layer on the surface of various iron-based substrates through hydrothermal in-situ growth, eliminating the need for binders and conductive agents, thus avoiding the defects of traditional powder electrodes such as poor interfacial contact, easy detachment of active materials, and high interfacial impedance. The integrated conductive framework structure effectively accelerates iron ion transport kinetics, achieving uniform nucleation and stable intercalation / deintercalation of iron ions, significantly inhibiting hydrogen evolution corrosion and disordered dendrite growth of the iron anode, greatly improving the electrochemical reversibility and structural stability of the iron anode, effectively extending the cycle life of aqueous iron metal batteries, and possessing excellent electrochemical performance and broad commercial energy storage application prospects. Attached Figure Description
[0013] Figure 1 The image shows the XRD pattern of the surface-grown sodium iron phosphate foam prepared in Example 1.
[0014] Figure 2 SEM image of sodium iron phosphate foam prepared in situ on the surface in Example 2.
[0015] Figure 3 The activation energy fitting curves are shown for the sodium iron phosphate modified foamed iron electrode and the pure foamed iron electrode.
[0016] Figure 4 Linear sweep voltammetry curves of sodium iron phosphate modified foamed iron anode and pure foamed iron anode are compared.
[0017] Figure 5 Tafel polarization curves of sodium iron phosphate modified foamed iron anode and pure foamed iron anode are compared.
[0018] Figure 6 To test the symmetric cell assembled using sodium iron phosphate modified foamed iron anode and pure foamed iron anode at 1 mA cm⁻¹ -2 Cycle life comparison curves at current density. Detailed Implementation
[0019] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments, but this should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following embodiments are commercially available unless otherwise specified. Example
[0020] Preparation of in-situ grown sodium ferric phosphate foam matrix: Commercial three-dimensional porous foamed iron samples with dimensions of 20mm × 30mm × 2mm were cut. The foamed iron was ultrasonically cleaned in anhydrous ethanol for 8 minutes to remove surface oil. Subsequently, it was ultrasonically acid-washed with 0.5mol / L dilute hydrochloric acid solution for 1 minute to remove the original oxide layer on the surface. After acid washing, the sample was repeatedly rinsed with deionized water until the pH of the washing solution was neutral. The sample was then immersed in anhydrous ethanol for 3 minutes, removed, and dried at 60℃ to obtain activated foamed iron. At room temperature, 10mL of deionized water and 10mL of ethylene glycol were mixed to prepare a mixed solvent. Sodium dihydrogen phosphate solid was weighed and added to the mixed solvent. The mixture was magnetically stirred until the solid was completely dissolved to prepare a sodium dihydrogen phosphate precursor solution with a concentration of 4mol / L. The activated foamed iron was completely immersed in the sodium dihydrogen phosphate precursor solution and then transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and sealed. The reactor was placed in an oven and the temperature was set at 225℃ for 12 hours to carry out the hydrothermal in-situ growth reaction. After the hydrothermal reaction is completed, the oven is turned off and the reactor is allowed to cool naturally to room temperature. The sample is then taken out and rinsed three times with deionized water and twice with anhydrous ethanol. The rinsed sample is then placed in a drying oven at 50°C and dried for 20 minutes to obtain the in-situ grown sodium iron phosphate foam matrix.
[0021] In-situ growth of sodium iron phosphate foam matrix for symmetric cell assembly and electrochemical testing: Battery assembly: The in-situ grown sodium iron phosphate foam iron matrix prepared in Example 1 was directly used as the negative and positive electrodes of the aqueous iron metal battery. The symmetrical battery was assembled and tested with the matching separator (Whatman glass fiber separator) and 1 mol / L ferrous sulfate aqueous electrolyte without the need for additional binders or conductive agents for coating and sheet preparation.
[0022] (2) Oxygen-free protection treatment: In order to reduce the oxidation of ferrous ions in the electrolyte by oxygen in the air, the battery cavity is continuously purged with argon gas and completely sealed after the battery is assembled, and an oxygen-free test environment is maintained throughout the process.
[0023] The assembled aqueous iron-metal battery was placed in a battery electrochemical testing system for constant current charge-discharge cycle testing. Test conditions: constant current charge-discharge cycle testing; voltage test range set according to the standard window for aqueous iron-metal batteries. Material characterization and electrochemical test results are shown in Figure 1. Figure 2 As shown. By Figure 1 It can be seen that all diffraction peaks of the product highly match the standard card of sodium ferric phosphate in the ferrophosphate phase, with no impurity phases formed, indicating excellent material crystallinity; Figure 2 It can be observed that the sodium iron phosphate active material is uniformly and completely coated on the surface and internal pores of the foamed iron, with a tight bond and no large-area shedding. Electrochemical test results show that the in-situ grown sodium iron phosphate foamed iron anode of this invention has extremely low charge transfer impedance, fast iron ion intercalation and deintercalation kinetics, and weak capacity decay during long-term cycling. This proves that the three-dimensional conductive framework of the foamed iron and the composite structure of in-situ grown sodium iron phosphate can effectively inhibit the pulverization and shedding of active material, and significantly improve the cycling stability of the anode in aqueous iron-metal batteries.
[0024] Comparative Example 1 Electrode of pure foamed iron blank control group: To verify the effect of in-situ growth of sodium iron phosphate composite structure on electrode performance, blank foamed iron was prepared as a control electrode after only pretreatment and without hydrothermal loading of sodium iron phosphate.
[0025] Specific preparation method: The same process as in Example 1 is followed to complete the degreasing, acid washing, water washing, drying and activation of the foamed iron. The process of soaking in the precursor solution and high-temperature hydrothermal in-situ growth is not carried out. The blank foamed iron is directly used as the negative electrode to assemble an aqueous iron metal battery.
[0026] Charge-discharge tests were conducted under the same anaerobic environment and electrochemical test parameters as in Example 2. The test results showed that the blank pure foamed iron had extremely low iron storage capacity, high electrochemical impedance, slow iron ion stripping and deposition kinetics, and rapid capacity decay during long-cycle processes. Its overall electrochemical performance was far inferior to that of the in-situ grown sodium iron phosphate foamed iron substrate anode in Example 1.
[0027] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Various changes and modifications can be made to the present invention without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of the present invention as claimed.
Claims
1. A method for preparing a binder-free sodium iron phosphate modified iron anode, characterized in that... The specific preparation steps are as follows: a sodium dihydrogen phosphate precursor mixed solution is prepared, and sodium iron phosphate active material of ferrophosphate mineral phase is grown in situ on the surface and internal channels of an iron-based conductive substrate using a hydrothermal synthesis process. The iron-based conductive substrate is foamed iron. After the hydrothermal reaction is completed, the substrate is cooled to room temperature, and then cleaned and dried to obtain sodium iron phosphate modified iron anode. This sodium iron phosphate modified iron anode is directly used as a negative electrode sheet for assembling aqueous iron-metal batteries. The continuous high-speed conductive network constructed by the three-dimensional interconnected iron-based conductive substrate makes the interface between the sodium iron phosphate active material and the iron-based conductive substrate firmly bonded, inhibiting the pulverization, shedding and peeling of the active material during charging and discharging. The in-situ grown sodium iron phosphate mineral phase has good hydrophilicity, which helps the desolvation of ferrous ions, effectively optimizes the ion transport behavior at the electrode interface, reduces the interface impedance, accelerates the electrochemical kinetic reaction, and thus significantly improves the reversible capacity and long-cycle stability of aqueous iron-metal batteries.
2. The method for preparing the binderless sodium iron phosphate modified iron anode according to claim 1, characterized in that: The concentration of the sodium dihydrogen phosphate precursor mixed solution is 2~5 mol / L, and its solvent is a mixed solvent system of deionized water and ethylene glycol with a volume ratio of 0.5~4:
1.
3. The method for preparing the binderless sodium iron phosphate modified iron anode according to claim 1, characterized in that: The pretreatment process of the iron-based conductive substrate is to soak and activate the iron-based conductive substrate with dilute hydrochloric acid solution to remove the oxide layer and impurities on the surface of the iron-based conductive substrate. The concentration of the dilute hydrochloric acid solution is 0.5~2mol / L, and the soaking and activation time is 30~120s. After soaking and activation, the iron-based conductive substrate is cleaned alternately with deionized water and ethanol and then dried for later use.
4. The method for preparing the binderless sodium iron phosphate modified iron anode according to claim 1, characterized in that... The specific process of the hydrothermal synthesis is as follows: the pretreated iron-based conductive matrix is completely immersed in a sodium dihydrogen phosphate precursor mixed solution, and then transferred to a hydrothermal reactor for hydrothermal reaction at 200~230℃ for 8~14h.
5. The application of the binder-free sodium iron phosphate modified iron anode prepared by the method according to any one of claims 1 to 4 in the assembly of aqueous iron metal batteries.
6. The application according to claim 5, characterized in that: The aqueous iron-metal battery is either an aqueous iron-metal symmetrical button cell or an aqueous iron-metal full cell. The aqueous iron-metal symmetrical button cell uses an aqueous solution of ferrous sulfate as the electrolyte, and sodium iron phosphate modifies the iron anode as the positive electrode, which is then assembled with a glass fiber separator to complete the symmetrical button cell assembly. The aqueous iron-metal full cell system uses an aqueous solution of ferrous sulfate as the electrolyte, and an iron-based Prussian blue analogue or elemental sulfur as the positive electrode, which is then assembled with a glass fiber separator to complete the full cell assembly.
Citation Information
Patent Citations
Alkaline secondary battery iron-based negative plate and preparation method thereof and alkaline secondary battery provided with iron-based negative plate
CN109786745A
Low-temperature-resistant aqueous nickel-iron battery
CN114171807A
Chlorine salt corrosive liquid, iron negative electrode and preparation method of iron negative electrode
CN119571327A